Impact of previous biologic use on the efficacy and safety of brodalumab and ustekinumab in patients with moderate‐to‐severe plaque psoriasis: integrated analysis of the randomized controlled trials AMAGINE‐2 and AMAGINE‐3. (1st August 2018) - Papp, K.A.; Gordon, K.B.; Langley, R.G.; Lebwohl, M.G.; Gottlieb, A.B.; Rastogi, S.; Pillai, R.; Israel, R.J.
Summary: Background: Biologics are being used increasingly to treat moderate‐to‐severe psoriasis. Efficacy may differ in patients with previous exposure to biologics. Objectives: To investigate the impact of previous biologic exposure on the efficacy and safety of brodalumab and ustekinumab in patients with moderate‐to‐severe plaque psoriasis. Methods: Two placebo‐ and ustekinumab‐controlled phase III clinical trials. There was an initial 12‐week induction phase where patients were treated with brodalumab [210 mg or 140 mg every 2 weeks (Q2W)], ustekinumab or placebo. Efficacy end points included ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) and static Physician's Global Assessment (score of 0 or 1) vs. placebo, PASI 100 vs. ustekinumab, Dermatology Life Quality Index and Psoriasis Symptom Inventory. Adverse events were monitored throughout. Results: In total, 493 patients [334 (27%) brodalumab 210 mg Q2W and 159 (26%) ustekinumab] had received prior biologics; 150 (12%) and 62 (10%), respectively, reported previously failed treatment with a biologic. Brodalumab efficacy in patients with or without previous exposure to biologics was statistically equivalent: 40·9% and 39·5% of biologic‐naive and ‐experienced patients achieved PASI 100 at week 12, compared with 21·1% and 17·0% with ustekinumab (both P < 0·001). In patients where prior biologics had been successful or failed, 41·7% and 32·0% achieved PASI 100, compared with 21·1% and 11·3% with ustekinumab. Tolerability was similar, and did not appear to be influenced by previous treatment with biologics. Conclusions: The efficacy of brodalumab 210 mg Q2W was similar regardless of prior biological therapy ( P = 0·31, 0·32 and 0·64 for PASI 75, 90 and 100, respectively). Almost twice as many patients achieved PASI 100 or complete clearance with brodalumab at week 12 compared with ustekinumab; the differences were most noticeable where previous biologics had failed. Both treatments were well tolerated.